Monoclonal antibodies against influenza viruses: a clinical trials review - Mota, Kenneth Gabriel; Moro, Ana Maria (Frontiers in Immunology, 2025)
The zoonotic influenza viruses cause seasonal epidemics and occasional pandemics, posing a significant public health threat. Transmitted by influenza A and B viruses, they result in ~1 billion annual infections, 3–5 million severe cases, and 300,000–500,000 deaths worldwide, with U.S. healthcare costs reaching $87.1 billion yearly. Understanding viral biology is crucial for developing effective treatment and prevention strategies. This review analyzes 27 clinical trials of anti-influenza monoclonal antibodies (mAbs) from ClinicalTrials.gov, assessing their therapeutic and prophylactic potential. Some mAbs target conserved viral regions (e.g., hemagglutinin stem, M2e protein) for broad-spectrum neutralization. MHAA4549A demonstrated a 97.5% reduction in viral load in H3N2 models and showed synergistic effects with oseltamivir in severe cases. However, despite preclinical promise, others, such as VIR-2482 (intramuscular) and MEDI8852, failed in Phase 2 trials. Safety profiles were generally favorable, with mild Emergent Adverse Events (EAEs) (headache, gastrointestinal disturbances). Key challenges include poor mucosal tissue penetration and variable clinical responses. While mAb-oseltamivir combinations accelerated recovery in hospitalized patients, larger cohorts lacked statistical significance. Viral evolution remains a significant hurdle, emphasizing the need to target conserved epitopes. Future strategies may optimize half-life (e.g., Fc modifications in VIR-2482), improve mucosal delivery, and integrate mAbs with vaccines/antivirals. mAbs hold promise for high-risk groups and pandemics but require further engineering to enhance efficacy and overcome biological barriers. Refinements in administration and design could establish monoclonal antibodies (mAbs) as a key tool in the management of influenza.